LEGISLATION DEROGATING FROM THE QUEBEC CIVIL CODE - Larouche, Angers (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1983)
The author studies how, by the introduction of Statute Law in Civil matters, the Civil Code is been modify. He focuses mainly on the Consumer Protection Act, the Charter of Rights and Freedoms, the Workmen’s Compensation Act, the Automobile Insurance Act, and other Statutes that either derogate, complete or enlarge the scope of the provisions of the Civil Code.